Bilateral facial nerve palsy as a rare presentation of systemic lupus erythematosus - Tagru Raju; Tulika Garg; Jaspreet Kaur; Monica Gupta (APIK Journal of Internal Medicine, 2024)
Systemic lupus erythematosus (SLE), a disease of the immune system, has a relapsing-remitting course. It is known to affect multiple organ systems of the body, including the nervous system. Cranial neuropathy, particularly facial neuropathy, is an unusual complication of SLE whose pathogenic mechanism is still not understood. Cardiac involvement, like myocarditis and papilledema, is another rare presentation of SLE. A 23-year-old male had bilateral lower motor neuron type of facial palsy which on a thorough investigation was found to be as a manifestation of SLE confirmed by antinuclear antibodies and double-stranded DNA antibody positive test. Electrocardiogram and echocardiography were suggestive of myocarditis. Fundus examination revealed Grade 2 papilledema. The patient was managed with symptomatic treatment along with corticosteroids, to which he responded gradually. Bilateral facial nerve lower motor neuron type palsy is a rare manifestation of SLE which should be diagnosed promptly and can be managed with corticosteroids. The clinician should also keep an eye on infrequent manifestations like myocarditis and papilledema.